1989
DOI: 10.1007/bf00558152
|View full text |Cite
|
Sign up to set email alerts
|

Enalapril and hydrochlorothiazide in hypertensive Africans

Abstract: The antihypertensive efficacy both of angiotensin converting enzyme (ACE) inhibitors and thiazide diuretics has been claimed to be influenced by plasma renin activity, which declines with age and is low in blacks. In a double-blind, placebo-controlled, double-dummy, randomized, parallel-group preliminary study, the antihypertensive efficacy and tolerability of the ACE inhibitor enalapril (20 mg day-1) and hydrochlorothiazide (50 mg day-1) were evaluated and compared for 4 weeks in 20 African patients with esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 21 publications
1
21
1
Order By: Relevance
“…Our findings, therefore, are consistent with a number of other reports (13,14) which indicate that at best body dimension only exerts a minor difference in BP in some paediatric population. Of note, the literature suggests that over-weight is not a common concomitant of elevated BP in adult Nigerians (15)(16)(17). Therefore, our findings reinforce the position (13,14) that in some populations, the influence of body size on BP in relation to other factors, such as age and heredity may have been overstated.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings, therefore, are consistent with a number of other reports (13,14) which indicate that at best body dimension only exerts a minor difference in BP in some paediatric population. Of note, the literature suggests that over-weight is not a common concomitant of elevated BP in adult Nigerians (15)(16)(17). Therefore, our findings reinforce the position (13,14) that in some populations, the influence of body size on BP in relation to other factors, such as age and heredity may have been overstated.…”
Section: Discussionmentioning
confidence: 99%
“…12 Since our therapeutic audit in 1989, 12 novel antihypertensive drugs such as calcium antagonists 13,14 and angiotensin-converting enzyme inhibitors (ACEIs) 14,15 have been introduced into routine clinical practice in Nigeria. In our earlier study, 12 we highlighted the much more dismal prognosis of patients with concurrent hypertension with diabetes, which has been confirmed in a more recent study.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies [8,10,17] in Nigeria showed that daily doses of hydrochlorothiazide (HCTZ) as high as 50 mg alone or 100 mg in combination with amiloride (Moduretic ® ) or K + supplementation effectively lower BP without metabolic side effects, e.g. hypokalaemia or glucose intolerance.…”
mentioning
confidence: 99%
“…Part of the problem may be linked to the routine use of newer antihypertensive drugs such as · 1 -adrenergic blockers and angiotensin-converting enzyme (ACE) inhibitors, which are held to be more desirable for the treatment of hypertension in diabetes; however, these categories of medications are relatively ineffective in Nigerians and other black Africans [8][9][10][11][12] and are also far more expensive than thiazides. In contrast, thiazides are relatively more effective in black Africans and are also widely available and cheap [5][6][7][8][9][10][11], but are hardly prescribed for diabetics with hypertension, probably for fear of inducing hypokalaemia and aggravating the control of existing diabetes [13][14][15][16].…”
mentioning
confidence: 99%